ANALISIS PENERAPAN SAK 109 PADA LEMBAGA AMIL ZAKAT, INFAQ DAN SHADAQAH MUHAMMADIYAH MALANG - Hidayat, Ryan; Syamsul Bahri; Zainudin, Zainudin (Journal of Innovation Research and Knowledge, 2023)
This study aims to determine the implementation system of PSAK 109 concerning zakat, infaq and alms at the Amil Zakat, Infak and Shadaqah Muhammadiyah Malang Institute. The research method used in this study is descriptive qualitative research, namely a research method that utilizes qualitative data and is described descriptively. Institute of Amil Zakat, Infak and Sadaqah Muhammadiyah Malang as objects in this research. Primary data was obtained from documents contained in the Amil Zakat, Infak and Shadaqah Muhammadiyah Malang Institute. In addition, interviews were conducted with those concerned and direct observation. The results of this study indicate that the Amil Zakat, Infak and Sadaqah Muhammadiyah Malang Institute has used financial reports in accordance with PSAK 109 which regulates zakat, infaq and alms.